Pengaruh Customer Orientation, Service Quality, dan Brand Image Terhadap Customer Satisfaction - Sheva Ardhiansyah (MES Bogor, 2026)
In the fast food industry, customer satisfaction is a key factor in maintaining business sustainability amid increasingly fierce competition. The purpose of this study is to explore the influence of customer orientation, service quality, and brand image on customer satisfaction among fast food consumers in the Bekasi area using a quantitative method through multiple linear regression with a total of 132 respondents. The results of the study indicate that customer orientation has a direct impact on customer satisfaction, service quality has a direct impact on customer satisfaction, and brand image has a positive impact on customer satisfaction. These findings indicate that customer satisfaction can be achieved through the simultaneous interaction of customer orientation, service quality, and brand image. The implications of this study emphasize that fast-food companies need to consistently apply customer orientation by understanding consumer needs and expectations, improving service quality in terms of speed, accuracy, comfort, and cleanliness, and maintaining brand image consistency through customer experiences aligned with brand identity. By managing these three factors simultaneously, companies can not only enhance customer satisfaction but also strengthen loyalty and encourage positive recommendations, which are highly influential in addressing industry competition.